2022
DOI: 10.1002/eat.23788
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on adolescents with eating disorders: Increased need for medical stabilization and decreased access to care

Abstract: Objective We aimed to identify trends of patients with eating disorders (EDs) requiring hospitalization before and during the pandemic at a children's hospital in the southeastern United States. Method A retrospective chart review was completed for 71 adolescents and young adults (ages 10–21 years; M = 14.61, SD = 2.121). Results Results indicated a 188% increase in ED hospital admissions since the pandemic, with patients presenting with increased rates of comorbid mental health diagnoses (p = .009). During CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Earlier pandemic studies noted higher medical acuity in patients hospitalized with ED in the first year of the pandemic as well as increased or new self‐reported restrictive symptomatology directly attributed to the pandemic and quarantine measures (Agostino et al, 2021; Asch et al, 2021; Feldman et al, 2023; Haripersad et al, 2021; Hartman‐Munick et al, 2022; Lin et al, 2021; Otto et al, 2021; Parsons et al, 2021; Shum et al, 2022). Prolonged disruption of daily routines and constraints on out‐of‐home activities, especially cessation of athletic programs and gym restrictions, may have increased weight or body image concerns, thereby negatively impacting eating, exercise, and mental resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier pandemic studies noted higher medical acuity in patients hospitalized with ED in the first year of the pandemic as well as increased or new self‐reported restrictive symptomatology directly attributed to the pandemic and quarantine measures (Agostino et al, 2021; Asch et al, 2021; Feldman et al, 2023; Haripersad et al, 2021; Hartman‐Munick et al, 2022; Lin et al, 2021; Otto et al, 2021; Parsons et al, 2021; Shum et al, 2022). Prolonged disruption of daily routines and constraints on out‐of‐home activities, especially cessation of athletic programs and gym restrictions, may have increased weight or body image concerns, thereby negatively impacting eating, exercise, and mental resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Research through the first year of the pandemic in both pediatric and adult literature reported increased rates of ED‐related encounters across healthcare environments. Concerns for worsening medical acuity of patients, especially with restrictive or compensatory behaviors like AN and BN, have been reported using encounter rates, hospitalization rates, and/or longer duration of stay as indirect markers of medical severity (Agostino et al, 2021; Asch et al, 2021; Feldman et al, 2023; Haripersad et al, 2021; Hartman‐Munick et al, 2022; Lin et al, 2021; Otto et al, 2021; Parsons et al, 2021; Shum et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1 in 10 Americans will struggle with an ED during their lifetime (5). Like many mental health conditions, the pandemic response increased ED hospital visits twoto threefold compared with the previous years and has been particularly difficult for teenagers (6)(7)(8). Moreover, higher social media engagement, specifically photo-based platforms, is associated with an increased in ED behaviors (9).…”
Section: A Brief Overview Of Edsmentioning
confidence: 99%
“…However, many people with these disorders do not fully recover after CBT (Linardon & Wade, 2018), or are unable to access CBT, as it is typically provided in specialist centers (Kazdin et al, 2017; Kazdin & Blase, 2011; Regan et al, 2017). Further limiting treatment accessibility is the rising prevalence of EDs (van Hoeken & Hoek, 2020; Zipfel et al, 2022), putting high stress on the capacity of specialized treatment facilities (Feldman et al, 2023; Katzman, 2021). As such, there is a need to develop scalable, effective, and acceptable therapies that can be delivered with minimal barriers.…”
Section: Introductionmentioning
confidence: 99%